Serum from Nipah virus patients recognises recombinant viral proteins produced in Escherichia coli - Tiong, Vunjia; Lam, Chui Wan; Phoon, Wai Hong; AbuBakar, Sazaly; Chang, Li Yen (Institute of Infectious Diseases, 2017)
The genes for Nipah virus (NiV) proteins were amplified from viral RNA, cloned into the plasmid pTriEx-3 Hygro, expressed, and purified using immobilized metal affinity chromatography. The recombinant N, F, and G NiV proteins (rNiV-N, rNiV-F, and rNiV-G), were successfully expressed in Escherichia coli and purified with a yield of 4, 16, and 4 mg/L, respectively. All 3 recombinant viral proteins reacted with all 19 samples of NiV-positive human sera. The rNiV-N and rNiV-G proteins were the most immunogenic. The recombinant viral proteins did not react with any of the 12 NiV-negative sera. However, serum from a patient with a late-onset relapsing NiV infection complication was found to be primarily reactive to rNiV-G only. Additionally, there is a distinctive variation in the profile of antigen-reactive bands between the sample from a case of relapsing NiV encephalitis and that of acute NiV infection. The overall findings of this study suggest that the recombinant viral proteins have the potential to be developed further for use in the detection of NiV infection, and continuous biosurveillance of NiV infection in resource-limited settings.